IMPLEMENTASI DESENTRALISASI PENDIDIKAN TERHADAPOTONOMIDAERAH - Sugiyanto Sugiyanto (LPMPP Universitas Negeri Yogyakarta, 2001)
l7te essence of education desentralization is transfer tlte entire or a part autl10ritymanagement education service from central government to local government unit. Educationdecentralization must be answer local development situation and condition, necessity andvalues in the regional.Tile educ tion is Wllich determines economic growth/ as a part ofdevelopment process,Tile education an investation of human resourses development will increase ability and skillagree with community necessity aspiration and development.Local financial sector is very influence to education decentralization existense, becauselocal governn1ent must be assume liabilityfor cost education.